The morality of security: a theory of just securitisation - Floyd, R; Loader, I; Wolfendale, J; de Londras, F; Roe, P (Cambridge University Press, 2022)
The purpose of this introduction is to concisely present The Morality of Security: A Theory of Just Securitization so that those unfamiliar with this work are better able to engage with the symposium. The book develops a Theory of Just Securitisation outlining when securitisation is morally permissible. Securitisation, here, refers to more than a securitising speech act coupled with a legitimising audience's tacit or actual acceptance of the threat and defence framing. Arguably the question of the morality of securitisation is most pertinent when the same encompasses the use of measures and conduct that most reasonable persons would ordinarily (that is, in times when there is no relevant threat) consider unacceptable, largely because of the harm and/or the violence risked or entailed.